Discussion: The effect of surface roughness and shear rate during fall-cone calibration - O'Kelly, Brendan (My University, 2022)
The fall-cone test is one of the most popular methods used to characterise fine-grained soils. Traditionally, the fall-cone has been used to determine the liquid limit. However, the undrained shear strength of a given soil can be related to the penetration depth based on Hansbo's cone factor K. Specifically for the 30° cone, a wide number of different K values are reported in the literature, ranging from 0·5 to 1·33. It has been consistently argued that the cone surface roughness is one of the main reasons for the divergence. In the first part of this paper, four different cone surfaces were tested under similar conditions with three different soils; the experimental evidence shows that the cone surface roughness does not have a major effect on the fall-cone penetration. Instead, different shear rates during calibration procedures are mainly responsible for diverging K values. In the second part of the paper, experimental evidence from this work and that of several other authors are used to define an empirical expression to determine K. A Bayesian technique was used to quantify the uncertainty of the empirical parameters estimated during the process. The fitted results are reported with the relevant statistical uncertainty. It is expected that the proposed equation would provide engineers with a tool to better define a K value.
PUBLISHED
Keywords: Smart & Sustainable Planet; Atterberg limits; Geotechnical Engineering; Geotechnics; SOIL PARAMETERS; SOIL PROPERTIES; SOIL TYPE; Soil Mechanics; Soil Mechanics & Foundations; geotechnical; soil classification